Pedotransfer functions for water retention in different soil classes from the center-southern Rio Grande do Sul State Funções de pedotransferência para retenção de água em diferentes classes de solos no centro-sul do estado do Rio Grande do Sul - Walbert Júnior Reis dos Santos; Nilton Curi; Sérgio Henrique Godinho Silva; Elias Frank de Araújo; João José Marques (Ciência e Agrotecnologia, 2013)
Water retention in soil is used in many agronomic and environmental applications, but its direct measurement is time-consuming and expensive. Therefore, pedotransfer functions (PTFs) are alternatives to obtain this information faster and more economically. The objectives of this study were to generate and validate PTFs to estimate the water content at potentials of -33 kPa (field capacity) and -1500 kPa (permanent wilting point) for different soil classes from the central-south portion of Rio Grande do Sul State. The physical and chemical analyses database from soil surveys of the Celulose Riograndense Corp were used. The database is composed of particle size distribution (coarse and fine sand, silt and clay), soil organic matter, and water content data at the above mentioned potentials, besides other information concerning the behavior of the soil classes at field conditions. Firstly, the data were stratified by soil classes and depths, and then 70% of the data were separated for PTF generation and 30% for validation. PTFs were generated for each specific soil class and also general PTFs which were not stratified by soil class, by means of stepwise multiple regression. In most situations, PTFs for a specific soil class showed a better fit than the general PTFs. Proper adjustment of the data showed that the water retention values at potentials of -33 kPa and -1500 kPa can be estimated for the soils from the central-south portion of Rio Grande do Sul State that do not have such analyses through the use of PTFs. A retenção de água no solo é utilizada em diversas aplicações agronômicas e ambientais, porém sua medição direta consome tempo e dinheiro. Por isso, funções de pedotransferência (FPTs) são alternativas para a obtenção dessas informações de forma mais rápida e econômica. Neste trabalho, objetivou-se gerar e validar FPTs, para estimar o conteúdo de água nos potenciais de -33 kPa (capacidade de campo) e -1500 kPa (ponto de murcha permanente) para diferentes classes de solos na porção centro-sul do Rio Grande do Sul. Utilizou-se o banco de dados de análises físicas e químicas dos levantamentos de solos da empresa Celulose Riograndense, que é composto por dados de textura (areia grossa e fina, silte e argila), matéria orgânica do solo e dados de conteúdo de água nos potenciais supracitados, entre outras informações sobre o comportamento das classes de solo em condições de campo. Primeiramente, os dados foram estratificados por classes de solos e profundidades e, posteriormente, 70% dos dados foram separados para geração das FPTs e 30% para validação. Geraram-se FPTs específicas para cada classe de solo e também FPTs gerais, sem estratificação por classe de solos, por meio de regressão múltipla stepwise. Na maioria das situações, as FPTs específicas por classe de solo apresentaram melhor ajuste do que as FPTs gerais. Na maioria dos casos, o ajuste adequado dos dados demonstrou que os valores de retenção de água nos potenciais de -33 kPa e -1500 kPa podem ser estimados por meio de FPTs para os solos da porção centro-sul do Rio Grande do Sul que não possuem tais análises.